Manajemen Pada Zaman Rasulullah SAW - Elis Holisoh; Taufik Hidayat; Muhammad Rifki Al Asy’ari; Abdullah Sajidin; Yayat Hidayat; Anja Sugiarti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The function of proselytizing is not just advocacy, but proselytizing is basically a change in society. The movement for change cannot occur while in its place, but it must be managed properly and appropriately, requiring professionalism from missionary actors, especially those who work in missionary institutions. The Prophet (pbuh) showed great seriousness and concern in managing his vocations in Mecca and Medina. After a deeper study with the approach of management theory, it was found that the Prophet Saw. had carried out his proselytizing by applying management principles. Rasulullah Saw. as the leader of the people, has the ability to compile his proselytizing plans and strategies, he has been able to mobilize and motivate the companions during his proselytizing so that the entire Arabian Peninsula can accept the presence of Islam.